ҚАРАҚАЛПАҚ ФОЛЬКЛОРЫНЫҢ ДƟРЕТИЎШИЛЕРИ ҲӘМ АТКАРЫЎШЫЛАРЫ - Даулетмуратов, Ф.Б. (ILIM hám JÁMIYET, 2023)
The article describes the scientific and practical peculiarities and the role of the school of poetry and mentor apprentice programs in the development of Karakalpak epics.